Toxic food: commercial bear meat products are highly contaminated with lead (Pb) from hunting ammunition - Jon M. Arnemo; Adam F. G. Leontowich; Boris Fuchs; Helle B. Hydeskov; Ilia Rodushkin; Samantha Totoni; Cora Paulukat; Jordan O. Hampton (Exposure and Health, 2026)

Lead concentration in blood of Asian black bears in two areas of Central Japan - Koji Yamazaki; Mayumi Ishizuka; Shouta M.M. Nakayama; Nelly Banda; Shinsuke Koike; Yusuke Goto; Kozo Yamazaki; Yui Nemoto; Boris Fuchs; Jon M. Arnemo (Science of The Total Environment, 2025)

Toxic elements in arctic and sub-arctic brown bears: Blood concentrations of As, Cd, Hg and Pb in relation to diet, age, and human footprint - Boris Fuchs; Kyle Joly; Grant V. Hilderbrand; Alina L. Evans; Ilia Rodushkin; Lindsey S. Mangipane; Buck A. Mangipane; David D. Gustine; Andreas Zedrosser; Ludovick Brown; Jon M. Arnemo (Environmental Research, 2023)

Thermal and behavioural responses of moose to chemical immobilisation from a helicopter - Anne Randi Græsli; Alexandra Thiel; Larissa T. Beumer; Boris Fuchs; Fredrik Stenbacka; Wiebke Neumann; Navinder J. Singh; Göran Ericsson; Jon M. Arnemo; Alina L. Evans (European Journal of Wildlife Research, 2023)
Instrumentation and sample collection for wildlife research and management may require chemical immobilisation of animals, which may entail physiological and behavioural effects on them. It is therefore important to evaluate the immobilisation protocols to reduce the risk of mortality and morbidity of the handled animals and their populations. Using a multi-sensor approach, we assessed the short-term (< 10 days) thermal and behavioural responses of 10 adult female moose ( Alces alces ) equipped with ruminal temperature loggers and GPS collars with accelerometers to helicopter-based chemical immobilisations. We investigated the body temperature ( T b ), movement rates, and resting time before, during, and after recapture. Chemical immobilisations on average increased maximum T b by 0.71 °C during the capture day, and imposed longer travel distances during the capture day and the two following days (3.8 and 1.8 km, respectively), compared to a 10-day reference period before the immobilisation. The probability of resting was 5–6% lower on the capture day and the two following days compared to the reference period, and females with offspring had a higher probability of resting than females without. Maximum T b , movement rate, and resting time returned to pre-capture levels on an individual level 2 h, 3 days, and 3 days after the immobilisation, respectively. Chemical immobilisation of moose from a helicopter increases the energy expenditure deduced through movement and T b rise lasting for hours to days. Ecological and physiological studies aimed at inferring general patterns may encounter bias if including sensor and tracking data from tagged animals without accounting for potential post-capture effects.

Lead exposure in brown bears is linked to environmental levels and the distribution of moose kills - Ludovick Brown; Boris Fuchs; Jon M. Arnemo; Jonas Kindberg; Ilia Rodushkin; Andreas Zedrosser; Fanie Pelletier (Science of The Total Environment, 2023)

Reducing the risk of foaming and decreasing viscosity by two-stage anaerobic digestion of sugar beet pressed pulp - Elitza Stoyanova; Boris Forsthuber; Stefan Pohn; Christian Schwarz; Werner Fuchs; Günther Bochmann (Biodegradation, 2014)

Broad geographical distribution and high genetic diversity of shrew-borne Seewis hantavirus in Central Europe - Mathias Schlegel; Lukáš Radosa; Ulrike M. Rosenfeld; Sabrina Schmidt; Cornelia Triebenbacher; Paul-Walter Löhr; Dieter Fuchs; Marta Heroldová; Eva Jánová; Michal Stanko; Ladislav Mošanský; Jana Fričová; et al. (Virus Genes, 2012)